2017
DOI: 10.1111/grs.12186
|View full text |Cite
|
Sign up to set email alerts
|

Harvest regimen changes sericea lespedeza condensed tannin, fiber and protein concentrations

Abstract: Sericea lespedeza (Lespedeza cuneata [Dumont de Courset] G. Don.; SL) is a perennial, warm‐season legume containing condensed tannins (CT) that can play important roles in ruminant ecosystems. Our research objective was to determine season‐long average herbage CT fractions, crude protein (CP) and fiber concentrations under three harvest regimens for SL cv. AU Grazer at five locations within the southeastern USA during 2010. Harvest regimens were regrowth every 35 days (35‐day), previously uncut plots every 35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Concentrations of CT for the birdsfoot trefoil and sericea lespedeza were within the range of those previously found by Jonker and Yu (2017; 21-47 g/kg of DM) and Müir et al (2018; 121-142 g/kg of DM). However, alfalfa and crown vetch showed numerically higher CT concentrations than those reported by Jonker and Yu (2017; 0.5 g/kg of DM) and Terrill et al (1992; 16 g/kg of DM), respectively.…”
Section: Diet Composition and Donor Rumen Fluidsupporting
confidence: 89%
“…Concentrations of CT for the birdsfoot trefoil and sericea lespedeza were within the range of those previously found by Jonker and Yu (2017; 21-47 g/kg of DM) and Müir et al (2018; 121-142 g/kg of DM). However, alfalfa and crown vetch showed numerically higher CT concentrations than those reported by Jonker and Yu (2017; 0.5 g/kg of DM) and Terrill et al (1992; 16 g/kg of DM), respectively.…”
Section: Diet Composition and Donor Rumen Fluidsupporting
confidence: 89%
“…Shelton (1995, 1997) reported 1.8% condensed tannin in the dietary DM had minimal effect on rumen fermentation, mainly on minor VFA (isobutyrate, valerate, and isovalerate). In the present study, SLZ (condensed tannin containing; Muir et al 2018), and WCS (oil; Moore et al, 1986, and condensed tannin containing;Yu et al, 1993) resulted in similar VFA patterns while the BFT (contains condensed tannin; Min and Hart 2003) treatment exhibited higher overall VFA concentrations. Condensed tannins in SLZ forage have been reported to have a higher affinity for protein than tannins in BFT forages (Aerts et al 1999).…”
Section: Ph and Volatile Fatty Acidssupporting
confidence: 51%
“…Approximately 1 month before harvest it appeared that the level of lespedeza would be high, but based on the analyzed CT concentration compared with that in previous studies (Animut et al 2008a(Animut et al , 2008bPuchala et al 2012aPuchala et al , 2012b, apparently the level of grass had increased. However, Muir et al (2017) reported total CT levels of 6.1%-10.0% in Sericea lespedeza harvested at five locations in the southeastern USA.…”
Section: Dietsmentioning
confidence: 93%